„Fotoobrazy”, „fotogłosy” i „fotonarracje” w badaniach pedagogicznych - Nowotniak, Justyna (Studia Edukacyjne, 2018)
The dynamic development of the visual culture requires a revised approach and thinking about its role in didactic process and its presence in scientific research. The key goals of the author’s scientific interest in the different aspects of the visual aspect are as follows: to join the discussion on if and how to utilize photography in research on education, to rework the selected imaging techniques and analytical methods in this very context, and to carry out an interpretation of the visual material. The article references the outcomes obtained so far by an author.